Global assessment of its network dynamics reveals that polo-like kinase Plk1 inhibits the phosphatase PP6 to promote Aurora A activity - Kettenbach, Arminja N. (Sci Signal, 2018)
Polo-like kinase 1 (Plk1) is an essential protein kinase that promotes faithful mitotic progression in eukaryotes. The subcellular localization and substrate interactions of Plk1 are tightly controlled and require its binding to phosphorylated sequences. Here, to identify phosphorylation-dependent interactions within the Plk1 network in human mitotic cells we performed quantitative proteomics on HeLa cells cultured with kinase inhibitors or expressing a Plk1 mutant that was deficient in phosphorylation-dependent substrate binding. We found that many interactions were abolished upon kinase inhibition; however, a subset were protected from phosphatase opposition or were unopposed, resulting in persistent interaction of the substrate with Plk1. This subset includes phosphoprotein phosphatase 6 (PP6), whose activity towards Aurora kinase A (Aurora A) was inhibited by Plk1. Our data suggest that this Plk1-PP6 interaction creates a feedback loop that coordinates and reinforces the activities of Plk1 and Aurora A during mitotic entry and is terminated by the degradation of Plk1 during mitotic exit. Thus, we have identified a mechanism for the previously puzzling observation of Plk1-dependent regulation of Aurora A.